Developing Port Klang as National Load Centre and Regional Hub Through Synchronized Supply Chain and Efficient Port Operation - Fong, Loo Ming (2007)
The ocean covers more than two third of the earth’s surface and this provides immense maritime opportunities in marine transportation and trade. Ships that ply the maritime domain are primary mode of transportation and carry about 80% of the world trade volume (Organisation of Economic Cooperation and Development, OECD July 2003). Port Operations and ancillary services such as freight forwarding, shipping play an enormous role in generating economic growth. Seaborne trades through port terminal operations had attracted regional competitions for volume of cargo by sea. Ports such as Hong Kong, Japan, Singapore and also Malaysia are stepping up their efforts in improving port operations and increase efficiency in handling cargo in order to become world’s class port. The role of ports have been to facilitate efficient movement of goods in the global supply chain. Port Klang as national gateway has changed radically and dramatically into a major port not just handling a larger volume of national cargo but more significantly a port of international repute handling an increase volume of transhipment cargo as well. The hinterland logistics and infrastructures and synchronized supply chain will also need further attention as they play complementary and supporting role in Malaysia’s economy. Two of the exciting economy corridors had been launched notably the Northern Corridor Economic Region and Iskandar Development Region in December 2006 and July 2007 respectively (see appendix 2) These initiatives with commitment that involved more RM100 billions of development projects over the few years will certainly propel the National Load Centre agenda into greater height.Today’s globalised trade where physical movement of good and services are seamless and reduction in trade barriers, has posed some challenges on how business should be efficiently and effectively operate. The competitions are stiff and companies are competing fiercely and as result turning the market place into some “red ocean” a terminology used in the “Blue Ocean” Strategy . “Red ocean” describes companies trying to beat competition on same limited terrain where competitive advantange and survival are intensified to gain market share. To be able to compete globally terminal operators, logistics and supply chain participants should achieve operational excellence through meticulous planning and continuous improvement in efficient handling and in the process to reduce costs in the whole supply chain logistics. Port Klang will have to adopt competitive business model in order to sustain growth and continue foreign direct investment. Iskandar Development Region (IDR) had attracted some USD1.2 billions investment from middle east investors. In addition, Dubai World is preparing its masterplan for their interest in 2,255 acres of Tanjung Bin for industrial development as well as 500 acres near Port of Tanjung Pelepas for distripark and logistics (source http://www.idr.com.my) . Whilst this has generated much hype of the mammoth project in IDR, it’s too early to celebrate when the excellence in operation and competitive business environment remain lacklustre and not in tandem with such implementations. This paper shall conclude on the IDR and NCER initiatives and how this can be launching pad for Port Klang National Load Centre to generate more local cargo volume . East Malaysia i.e Sabah and Sarawak will also play significant role as the feeder service and connectivity continue to be improved and with more vessels plying the South China seas, hinterland infrastructure connection seem to be pivotal in moving forward. It will be interesting to see Kuantan as the east gateway for connectivity to Port Klang for East bound trade.